Acute autoimmune hepatitis mimicking metastatic liver disease: A case report - Masoodi, Ibrahim (Baishideng Publishing Group Co., Limited, 2012)
We report progressive painless jaundice in a 39 year old female with a suspicion of metastatic liver disease on ultrasound and computed tomography scan of the abdomen. Although the most frequent liver lesions are liver metastasis because of dual blood supply of the liver and the impact of hormones, the index case proved to have acute autoimmune hepatitis (AIH) after liver biopsy was undertaken. AIH, an unresolving inflammation of liver, occurs predominantly among females worldwide. It may present acutely and even fulminant hepatitis has been described. The index case had a dramatic response to steroid treatment with total recovery and complete resolution of liver lesions. She is clinically fine and has been regularly attending our clinic for the last year. To our knowledge from a Medline search, this is the first report where AIH was seen to mimic metastatic liver disease.